Needs and Supports in Transitional Housing for People Living with HIV/AIDS in Ontario, Canada. Issue 42 (26th May 2016) - Aguinaldo, Jeffrey P.; Ahluwalia, Amrita; Hambly, Keith; Koornstra, Jay; Rankin, Bruce; Roesslein, Kay
ABSTRACT: There is a paucity of research on transitional housing for people living with HIV/AIDS (PHA) and even less so within the Canadian context. The present work addresses that gap and reports on the results from the Transitional Housing Study, a province wide community-based research collaboration involving PHA, service providers, and university researchers in Ontario Canada. This article answers the following research questions: What supports do residents in transitional housing for PHA access and what needs do these supports address? Developing from a thematic analysis of in-depth qualitative interviews with 25 residents in one of three transitional housing agencies in Ontario for PHA, the findings reveal that participants benefited from four key supports while in transitional housing: the provision of a safe environment, co-coordination and management of HIV (and other) drug therapies, assistance with appointments, and referrals to health and social services. Until more resources are available to increase availability of transitional housing for PHA, the nonprofit housing sector must fill the gap that exists by offering the types of supports identified in this study in order to address the needs of PHA. Future research may link these supports efficiently with concrete health improvements and permanent housing stability among PHA.